2023
DOI: 10.1177/21514593231152172
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Oswestry Disability Index Cannot Reliably Predict Patient Satisfaction After Single and Double Level Lumbar Transforaminal Interbody Fusion Surgery

Abstract: Introduction The role of patient-reported outcomes in preoperative assessment is not well studied. There is recent interest in studying whether Patient-reported outcomes scores can be used either independently, or in conjunction with clinical findings, in the assessment of patients for surgery. Aims To investigate if improvement in clinically significant scores correlate with post-operative patient satisfaction in 1-2 level transforaminal lumbar interbody fusion (TLIF) surgery. We also aim to define a threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is interesting to note that 11% of patients, in our study, were dissatisfied despite a 30% or more improvement in ODI scores, and thus it is like the EQ-5D score, where there is likely a threshold of disability/inhibition of usual activities before patients become dissatisfied. Although improvements in ODI scores are associated with patient satisfaction ( Yee et al, 2020 ), discrepancies can be found between favourable postoperative ODI scores and patient satisfaction in the literature ( Azimi and Benzel, 2017 ), ( Teo et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that 11% of patients, in our study, were dissatisfied despite a 30% or more improvement in ODI scores, and thus it is like the EQ-5D score, where there is likely a threshold of disability/inhibition of usual activities before patients become dissatisfied. Although improvements in ODI scores are associated with patient satisfaction ( Yee et al, 2020 ), discrepancies can be found between favourable postoperative ODI scores and patient satisfaction in the literature ( Azimi and Benzel, 2017 ), ( Teo et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%